Field comparison test study of external shading effect on thermal-optical performance of ultralow-energy buildings in cold regions of China. (August 2020) - Huo, Huimin; Xu, Wei; Li, Angui; Cui, Guoyou; Wu, Yazhou; Liu, Changping
Abstract: External shading systems play a key role in reducing the solar radiation entering the buildings and improving the thermal and daylighting performance of buildings. This study aims to comprehensively investigate the external shading effect on thermal-optical performance of ultralow-energy buildings (UEBs) using field comparison test in cold regions of China. In particular, two identical real residential buildings are continuously monitored in a period: one as a reference zone and another as a study zone. The results highlight that the external shading device with different configurations can reduce indoor temperature fluctuations and the predicted mean vote ( PMV ) for UEBs during a hot summer. For non-air-conditioning conditions, the maximum temperature reduction of the shading zone is 0.8 °C, while the indoor temperature fluctuates within a small range of less than 2 °C. For air-conditioning conditions, external shading device with slats angle of 90° provides the best performance, with the energy-saving potential ( P ) of approximately 21.77%. In addition, as the slat angle ( SA ) and the shading to window ratio ( SWR ) decrease, the P decreases correspondingly. Moreover, the utilization of an external shading device does not have an absolute advantage in decreasing the indoor illuminance and eliminating indoor discomfort glare. If an external shading system significantly decrease the indoor luminance and illuminance, the external shading system may increase the indoor glare risk and fail to meet the indoor daylighting demand. Highlights: Field comparison test of ultralow-energy buildings were performed in cold regions. Thermal-optical comfort and energy-saving versus ten conditions were quantified. Shading effect of various configurations and fan-coil states were discussed. External shading system has a high energy-saving potential of up to 22%. External shading system may have a negative effect on natural lighting.